Pengaruh Profitabilitas, Ukuran Perusahaan, dan Dividend Payout Ratio terhadap Perataan Laba pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Setyowati, Anniza; Bone, Hamid; Iskandar, Iskandar (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
This research intend to analyze and determine the influence of profitability, firm size, and dividend payout ratio to the practice of income smoothing. Income smoothing is a management effort to reduce reported earnings fluctuations to make it look stable. The population in this research are manufacturing companies listed in Indonesia Stock Exchange during 2011-2015, as many in 125 companies. The sampling was done by using purposive sampling method, and acquired 28 companies as sample. The type of data in this research is quantitative data. While the data source used in this research is secondary data. The data were analyzed by using logistic regression analysis. The result of this research showed that profitability has negative and significant effects on the practice of income smoothing, while firm size and dividend payout ratio has not signification effect on the practice of income smoothing.